Student profile of youth and adult education of the city school of Pombal- PB - Silva, Francisco de Assis da; Costa, Caciana Cavalcanti; Sousa, Luci Cleide Farias Soares (Informativo Técnico do Semiárido, 2014)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">The present work aims to discuss the problem of the Education of Young People and adults in the context of the municipality of Pombal - PB reflecting on some of the factors that have prevented these young people and adults complete their studies on correct age. In view such considerations, the study aims to analyze the relationship of the EJA learners with the world of work, in order to discover through the profile of these students what are the real reasons that led them to leave and then return to the classroom. Thus the study was developed in distinct stages, namely: Study on the said topic, research and application of questionnaires with the middle school students of the School Monsenhor Vicente Freitas and School Arruda Câmara, located in the city of Pombal-PB. When analyzing the sample of individuals, was identified three distinct profiles: the first by young people who have never had interrupted their studies more who have had failures and now joined the EJA to complete the middle school with the lowest index of distortion of series/age; the second by adults who had interrupted their studies for any reason (work, marriage or pregnancy) and that are back-to-school with the aim of ending the middle school and even join a faculty in the perspective of a professionalization , and the third by young people who had interrupted their studies without apparent reasons or due to lack of incentive or by lack of interest. This work intends to collaborate with the development of the student of the EJA in Pombal Square through the junction of the EJA with the Solidary Economy, looking to improve on each learner group work and awakening solidarity.